Design de uma máquina de corte a laser que utiliza da tecnologia cnc com materiais de baixo custo - Lima, Vinícius Geraldo de (Universidade Federal Rural do Semi-Árido, 2018)
The CNC technology has improved the material processing, mostly for machining, enabling products development with greater quality, greater precision and higher production. The technology laser along with CNC is revolutionizing this study field. The present work consists in the development of a low-cost laser cutting machine that works with computer numerical command technology, to assist the “acceptor aerodesign” team on cutting balsa wood used on their prototypes development. For this purpose, it was used a bechmarking aiming to design a machine as efficient as the existing on the market; it was studied the laser machining process; stepper motor sizing; lazer power required to cut 1.5mm balsa wood using a predefined velocity, balancing this two interdependent parameters for a better cost benefit equilibrium; machine design with a 3D cad modeling using Autodesk Inventor PRO 2018 software. Finally, blueprints with parts number, materials and dimensions, resulting a compact, easy assembling and low cost project.
Monografia
Keywords: Madeira balsa; Tecnologia CNC; Corte a laser; Acceptor; Benchmarking; ENGENHARIAS::ENGENHARIA MECANICA